Endogenous Market Structures and Labor Market Dynamics - Andrea Colciago; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
We propose a flexible prices model where endogenous market structures and search and matching frictions in the labor market interact endogenously. The interplay between firms endogenous entry, strategic interactions among producers and labor market frictions represents a strong amplification channel of technology shocks on labor market variables, and helps addressing the unemployment-volatility puzzle. Consistently with U.S. evidence, new firms create a large fraction of new jobs and grow faster than more mature firms, net firms entry is procyclical and the price mark up is countercyclical.
Keywords: E24; E32; L11; 330; Endogenous Market Structures; Firms Entry; Search and Matching Frictions